Automated Weather Station measurements at Joyce Glacier, McMurdo Dry Valleys, 2008-2010 - Marte Gé Hofsteenge; Nicolas J Cullen; Carleen H Reijmer; Michiel R van den Broeke; Marwan Katurji; John Orwin (PANGAEA, 2025)
14-month record of automatic weather station (AWS) observations taken on Joyce Glacier in the McMurdo Dry Valleys. The data file includes both the variables measured at the AWS (relative humidity, temperature, radiation terms, wind speed and direction, surface height change) and surface energy balance and ablation terms derived from the AWS data using surface energy balance modelling (e.g. sensible and turbulent heat fluxes, surface and internal melt). The AWS was installed on Joyce Glacier at (-78.02075, 163.79346667), roughly 4000.167emm above sea level on 26 November 2008 and removed on 31 January 2010. Measurements were taken every 3000.167ems and stored as 150.167emmin averages on a data logger. The glacier tongue is located at the western end of the Garwood Valley, a coastal valley east of the Royal Society Range (about 250.167emkm from McMurdo Sound). The station was set up in the ablation zone of Joyce Glacier, about 1500.167emm from the north-east cliff. For more information about the variables and preprocessing see the corresponding paper.